The Virtual Teacher’s Lounge: How Teachers Meaningfully Connect Through Online Networks - Dunn, Randall (Proceedings of the International Conference on Networked Learning, 2008)
This study seeks to illuminate an understanding of naturally forming online communities of professional educators in the context of off-line communities. Essentially, an online discussion forum for educators is evaluated for the purpose of determining whether the forum provides a “space” conducive for the development of a community of professional educators as benchmarked against an understanding of offline community formation and existence. The primary approach to this study is qualitative in nature with some quasi-statistical support to elucidate analysis and conclusions. The study employs the use of QSR NVivo 7 to collect, catalogue, and analyze discussions from this online forum, examining discussions topically, contextually, and structurally – resulting in 4,211 postings split among 115 discussions made by 301 unique posters. An understanding of offline communities (as understood through the works of Ray Oldenburg, James Coleman, and Ferdinand Tonnies) is incorporated in the comparative analysis. The study finds that online communities closely resemble offline communities in structure and interaction, but only for select participants. These participants demonstrating or facilitating the characteristics of community comprise around 10% of the total number of users participating in the analyzed discussions. Those participants who did not participate heavily in discussions primarily remained in the more formal and professional set of exchanges, whereas those with higher levels of participation in the analyzed discussions participated both heavily in the more informal and “playful” discussions and in the more formal professional discussions, with the participation in the latter type taking on more of an "expert" role.